The ability to recognise emotions predicts the time-course of sarcasm processing: Evidence from eye movements - Henri Olkoniemi; Viivi Strömberg; Johanna K. Kaakinen (Sage, 2022)
A core feature of sarcasm is that there is a discrepancy between the literal meaning of the utterance and the context in which it is presented. This means that a sarcastic statement embedded in a story introduces a break in local coherence. Previous studies have shown that sarcastic statements in written stories often elicit longer processing times than their literal counterparts, possibly reflecting the difficulty of integrating the statement into the story’s context. In the present study, we examined how sarcastic statements are processed when the location of the local coherence break is manipulated by presenting the sarcastic dialogues either before or after contextual information. In total, 60 participants read short text paragraphs containing sarcastic or literal target statements, while their eye movements were recorded. Individual differences in ability to recognise emotions and working memory capacity were measured. The results suggest that longer reading times with sarcastic statements not only reflect local inconsistency but also attempt to resolve the meaning of the sarcastic statement. The ability to recognise emotions was reflected in eye-movement patterns, suggesting that readers who are poor at recognising emotions are slower at categorising the statement as sarcastic. Thus, they need more processing effort to resolve the sarcastic meaning.